(untitled) (Jurnal Manajemen Bisnis, 2024)
This research analyzes the influence of social media interactions on purchase intentions for Scarlett Whitening products, which are mediated by source credibility, homophily, and content quality. This study aims to understand how interactions on Instagram can influence purchase intentions. This research method uses a quantitative survey on 230 respondents, namely Scarlett Whitening users on the Instagram application in Indonesia. This research analysis uses the software SmartPLS by using the method Structural Equation Modeling (SEM). The results show that social media interaction has a positive and significant effect on source credibility, homophily, and content quality. Furthermore, homophily and content quality have a positive and significant effect on purchase intention, while source credibility does not have a significant effect on purchase intention. This research highlights the importance for Scarlett Whitening to not only actively interact with consumers but also pay attention to elements such as source credibility, homophily, and content quality to increase purchase intentions.